2021
DOI: 10.1021/acs.energyfuels.1c02941
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Oil Recovery Performance and Solution Properties of Hydrophobic Associative Xanthan Gum

Abstract: Xanthan gum (XG) is one of the widely used biopolymers in oilfield development. It has low cost and will not pollute the environment. However, its limited temperature and salt tolerance restricts its application in high temperature and high salt reservoirs. An environmentally friendly hydrophobic associative polymer was prepared by grafting long-chain alkyl groups onto xanthan gum through an etherification reaction for enhanced oil recovery (EOR). The hydrophobically modified xanthan gum (MXG) was characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 48 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…The appearance of the new bands indicated that welan gum was successfully modified using 1-bromohexadecane. The elongated bands associated with C–H and C–O–C bonds were also observed in 1-bromooctadecane-modified xanthan gum, compared with the xanthan gum precursor …”
Section: Results and Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The appearance of the new bands indicated that welan gum was successfully modified using 1-bromohexadecane. The elongated bands associated with C–H and C–O–C bonds were also observed in 1-bromooctadecane-modified xanthan gum, compared with the xanthan gum precursor …”
Section: Results and Discussionmentioning
confidence: 81%
“…The FTIR analysis (Figure a) showed a considerable difference in the bands among HWG, welan gum, and guar gum. The intensity of the bands associated with the C–H bond, appearing at 1416 cm –1 , substantially increased in HWG, compared to welan gum. , The increased intensity of the bands observed at 1416 cm –1 for HWG likely appeared because of the asymmetric configuration between the methyl groups connected to the long alkyl chain of HWG and original methyl groups present in the main HWG chain . The absorption band of C–H appearing at 2904 cm –1 also elongated for HWG, compared with that for the welan gum.…”
Section: Results and Discussionmentioning
confidence: 90%
See 3 more Smart Citations